Diversidad y estructura de ensamblajes tróficos de insectos inductores de agallas y parasitoides asociados a Quercus castanea a lo largo de un gradiente hídrico en la cuenca de Cuitzeo - Espinoza Olvera, Norma Angélica (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
Natural communities are structured by many organisms, which form complex biotic interactions (e. g. mutualists or antagonists interactions). Herbivory is a biotic antagonist interaction, particularly where the insects are recognized by consuming foliage of a wide variety of plant species. Herbivory is important in natural communities because it’s a factor that determines the structure and species composition of plants involving different ecological processes. Herbivory, in turn, can be affected by biotic (e. g. nutritional quality and plant defense) and abiotic factors (e. g. soil fertility and moisture availability) at different spatial and temporal scales. In this study, the effect of humidity (i. e. precipitation) and soil fertility on the structure and composition of gall-inducing insects associated with Quercus castanea was evaluated. We evaluated four study sites having an abiotic gradient of precipitation and soil fertility in which Q. castanea populations are present, this populations were located and selected in Cuitzeo Basin, Michoacán, Mexico. Using analysis of quantitative food webs, we evaluated trophic interactions of gall-inducing insects with their natural enemies (i. e. parasitoids) and with Q. castanea along the gradient. A positive relationship between annual rainfall and galls abundance was found at each study site. Furthermore, we found that abundance of galls in different organs (i. e branches vs. leaves) was spread along the water gradient and fertility, being the leaves galls the most abundant in all sites. No significant differences were found in wealth of galls between study sites, indicating that rainfall and soil fertility does not affect the wealth of this guild of insects. Finally, trophic web of gall-inducing insects Q. castanea were different according to the moisture gradient which changes in species composition, structure and resilience of the network exist, showing less moist.

Las comunidades naturales están estructuradas por diversos organismos, los cuales forman complejas interacciones bióticas (e.g. mutualistas o antagonistas). La herbivoría es una interacción biótica antagonista donde particularmente, los insectos son reconocidos por el consumo de las comunidades naturales ya que es un factor que determina la estructura y composición de los follajes de una gran diversidad de especies de plantas. La herbivoría es importante en comunidades especies de plantas vegetales que involucra diferentes procesos ecológicos. La herbivoría a su vez, puede ser afectada por factores bióticos (e.g. calidad nutricional y defensa vegetal) y por factores abióticos (e.g. fertilidad del suelo y disponibilidad de humedad) en diferentes escalas espacio-temporales. En este estudio, se evalúó el efecto de la humedad (i.e. precipitación) y de la fertilidad del suelo sobre la estructura y composición de los insectos inductores de agallas asociados a Quercus castanea. Cuatro sitios de estudio que presentan un gradiente abiótico de precipitación y fertilidad del suelo en los que se encuentran presentes poblaciones de Q. castanea, fueron ubicados y seleccionados dentro de la Cuenca de Cuitzeo, Michoacán, México. Mediante el uso de análisis de redes tróficas cuantitativas se evaluaron las interacciones tróficas de los insectos inductores de agallas con sus enemigos naturales (i.e. parasitoides) y con Q. castanea a lo largo del gradiente. Se encontró́ una relación positiva entre la precipitación media anual encontrada en cada sitio de estudio y la abundancia de agallas. Además, se encontró́ que la abundancia de agallas en los diferentes órganos (i.e. ramas vs. hojas) fue diferencial a lo largo del gradiente hídrico y de fertilidad, siendo las agallas de hojas las más abundantes para todos los sitios.
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FB-M-2014-0483; Agallas; Insectos; Parasitoides; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1712